Long Non-coding RNA TUSC7, a Target of miR-23b, Plays Tumor-Suppressing Roles in Human Gliomas - Shang, Chao; Guo, Yan; Hong, Yang; Xue, Yi-xue (Frontiers in Cellular Neuroscience, 2016)
TUSC7 (tumour suppressor candidate 7) gene belongs to long non-coding RNAs (lncRNAs), and is a novel potential tumor suppressor gene in several types of human cancers. Nevertheless, the expression and function TUSC7 in human brain glioma have not been elucidated. In this study, TUSC7 was confirmed to be low-expressed in tissues and cell lines of glioma, and the worse histological grade tended to have lower expression of TUSC7. Moreover, TUSC7 could be a biomarker for prognosis of glioma patients. Up-regulation of TUSC7 suppressed cell proliferation and invasive ability of glioma cells, and advanced cell apoptosis. Bioinformatics analysis and previous report showed TUSC7 could specifically combine with miR-23b. MiR-23b was up-regulated in glioma, its expression present a negative correlation with the expression of TUSC7. The expression of miR-23b could be inhibited remarkably by up-regulation of TUSC7 and the reciprocal inhibition was determined between TUSC7and miR-23b. Then, RNA pull-down assay and luciferase reporter assays were used to affirm that the sequence-specific connection between miR-23b and TUSC7. Meanwhile, TUSC7 inhibited the glioma cell proliferation, migration and invasive ability of glioma cells and promoted the cells apoptosis largely bypassing miR-23b expression alteration. Thus, we concluded that the lncRNA TUSC7 functions as a tumor suppress gene negatively regulated by miR-23b, may provided a novel therapeutic strategy for gliomas.